Financial Aspects of Integration in the Conditions of Formation of the Eurasian Economic Union - BERSTEMBAYEVA, Rysty; TLEUZHANOVA, Danagul; TOYZHIGITOVA, Zhanar; NURUMOV, Aldanysh; ORAZGALIYEVA, Araylim; KISHIBEKOVA, Galiya (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
The trends of globalization have invariably affected the financial sector. Financial globalization opens up opportunities for activating investment processes, developing domestic financial markets, and improving the quality of macroeconomic policies. At the same time, integration processes in the financial sector pose threats to the participating countries. At the same time, during the creation of the unified financial market, there are significant problems associated with uncoordinated measures of monetary, monetary, fiscal policy. Issues of the unification of legislation and organizational measures to regulate participants in the financial market and the development of payment systems are under consideration. They demand a solution to the problem of strengthening the coherence of measures in the field of financial regulation, taking into account the national interests of the countries participating in the Eurasian Economic Union.